DEVELOPMENT DASHBOARD HR LEARNING BASED OLAP IN LIFE INSURANCE COMPANY - William Frado Pattipeilohy; Sanwani Sanwani; Ade Priyatna (LPPM Nusa Mandiri, 2021)
Currently in the business world, companies have the challenge to survive and even thrive in the face of business changes that are so fast and flexible both in terms of markets, consumers, products to competitors. Companies are required to be able to take quick and appropriate decisions in the face of all these business changes. Implementation of Business Intelligence in a company becomes a real solution in facing all those challenges. Where by using Business Intelligence, management within a company can make appropriate decisions based on valid data that has been processed into knowledge and presented from various perspectives needed. This research developed an integrated system in the form of an OLAP-based dashboard to present data reports, especially in the Human Resources Division. Various data in the excel file upload are automatically generated by ETL to the database using SSIS and consolidated into a data warehouse. Processing using SSAS, which is displayed in the form of a dashboard using Reporting Services with a more interesting summary form. With the development of the HR Learning and Development dashboard, top-level management companies get reports for quick, precise and accurate decision making.